(untitled) (Bangladesh Journal of Medical Science, 2018)
In this case study the persistence of hypertension in a patient after successful coronary angioplasty was assessed. Pulse and blood pressure were recorded twice daily for 33 days at random interval. The results show the patient had high blood pressure for a total of 17 days in the 33 days of study period after Coronary Angioplasty and Stenting. The patient’s blood pressure never excided above 170/90 and pulse remained normal through the study period. In the case study multiple drugs failed to control blood pressure adequately. Other external factors may play a role in failure of management of BP. Indeed the patient’s lack of lifestyle modification as per advice of the physician may play a significant role in the persistence of hypertension. The patient should seek further medical assistance from specialists and drugs should be altered to control blood pressure adequately. Further investigation might be considered to rule out secondary causes of persistent hypertension. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.501-506